Analisa Stabilitas Perbaikan Dinding Penahan Tanah Eksisting pada Proyek Dermaga Veem Terminal Kalianget Kabupaten Sumenep - Aditya Dandy Firatama; Hafif Ahmad Abdul Aziz; Yuni Rokhmawati (G-Tech: Jurnal Teknologi Terapan, 2024)
Kalianget Pier has an important role in supporting goods delivery activities in the Sumenep Regency area.  There is a plan to improve the east side of the pier with the reinforcement of concrete soil retaining walls reinforced with Corrugated Concrete Sheet Pile and the addition of new pile caps. This study aims to determine the reliability of the repair of existing soil retaining walls in the project and obtain an efficient and safe design by using the quantitative method of the finite element method approach of the PLAXIS 2D auxiliary program so that the value of the safety factor that is reviewed globally and the internal force that occurs is obtained.  From the results of the stability analysis of the repair of the soil retaining wall of Kalianget Pier by reviewing several alternative repair methods, 2 methods are recommended, namely Alternative 1 repair (CCSP with reinforcement of Anchor Pile) and repair of Alternative 3 (SPSP with reinforcement of Anchor Pile). Of the two alternative repair methods, it has met the minimum value of soil retaining wall stability, so the design is safe to implement.